Peri-vascular adipose tissue attenuation on chest computed tomography in patients with Marfan Syndrome: a case series. - Tuttolomondo, Domenico; De Filippo, Massimo; Sartorio, Daniele; Nicolini, Francesco; Niccoli, Giampaolo; Gaibazzi, Nicola (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Marfan Syndrome is a genetic disorder that determines histopathological alterations of the aortic vascular wall leading to increased inflammatory component. The peri-vascular adipose tissue attenuation is a method able to capture localized vascular inflammation by mapping spatial changes of perivascular tissue attenuation on computed tomography. Methods. We measured peri-vascular adipose tissue attenuation around the ascending aorta in three consecutive subjects with confirmed genetic diagnosis of Marfan Syndrome. All subjects received the genetic diagnosis of fibrillin-1 gene mutation as part of the family screening of patients with known Marfan Syndrome. Chest computed tomography was performed in such asymptomatic subjects after genetic confirmation of Marfan Syndrome. None of these subjects showed aortic aneurysms or suffered from chronic inflammatory/infectious disease.Results. In the three subjects identified with Marfan Syndrome the value of aortic peri-vascular adipose tissue attenuation measured at chest computed tomography was higher than normal and the volume of aortic peri-vascular adipose tissue was lower.Conclusion. These preliminary observations suggest that peri-vascular adipose tissue attenuation is unexpectedly high in patients with Marfan Syndrome, notwithstanding the normal aortic diameter at the time of computed tomography. Whether this observation may find a clinical use in suspected Marfan Syndrome or in predicting aortic complications in Marfan Syndrome is worth to be assessed in prospective studies.